Effect of Time of Day on Sustained Postexercise Vasodilation Following Small Muscle-Mass Exercise in Humans - Brito, Leandro C.; Ely, Matthew R.; Sieck, Dylan C.; Mangum, Joshua E.; Larson, Emily A.; Minson, Christopher T.; Forjaz, Cláudia L. M.; Halliwill, John R. (Frontiers in Physiology, 2019)
Introduction: Previous studies observed diurnal variation in hemodynamic responses during recovery from whole-body exercise, with vasodilation appearing greater after evening versus morning sessions. It is unclear what mechanism(s) underlie this response. Since small muscle-mass exercise can isolate peripheral effects related to postexercise vasodilation, it may provide insight into possible mechanisms behind this diurnal variation. Methods: The study was conducted in ten healthy (5F, 5M) young individuals, following single-leg dynamic knee-extension exercise performed in the Morning (7:30-11:30am) or the Evening (5-9pm) on two different days, in random order. Arterial pressure (automated auscultation) and leg blood flow (femoral artery Doppler ultrasound) were measured pre-exercise and during 120 min postexercise. Net effect for each session was calculated as percent change in blood flow (or vascular conductance) between the Active Leg and the Inactive Leg. Results: Following Morning exercise, blood flow was 34.9 ± 8.9% higher in the Active Leg versus the Inactive Leg (p < 0.05) across recovery. Following Evening exercise, blood flow was 35.0 ± 8.8% higher in the Active Leg versus the Inactive Leg (p < 0.05). Likewise, vascular conductance was higher in the Active Leg versus the Inactive Leg (Morning: +35.1 ± 9.0%, p < 0.05; Evening: +33.2 ± 8.2%, p < 0.05). Morning and Evening blood flow (p = 0.66) and vascular conductance (p = 0.64) did not differ. Conclusions: These data suggest previous studies which identified diurnal variations in postexercise vasodilation responses are likely reflecting central rather than peripheral modulation of cardiovascular responses.